Penerapan Model Number Head Together Untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial Pada Siswa Kelas IX.3 MTsN 8 Aceh Besar - Asiah, Umi (Jurnal Cakrawala, 2024)
The purpose of this study is to improve the activities and learning outcomes of Social Sciences in class IX MTsN 8 Aceh Besar students for the 2018/2019 Academic Year. The model used in this class action research is the number head together model. The subjects of this class action study were students of class IX.3 MTsN 8 Aceh Besar with 35 students. This class action research was carried out in the 2018/2019 academic year. The methodology of this study is that class action research consists of two cycles and each cycle consists of two meetings. In each cycle consists of planning, execution, observation and reflection. The research procedure consists of pre-research, cycle one planning, implementation of cycle one action, cycle one observation, cycle one reflection, cycle two planning, execution of two cycle actions, two cycle observations and two cycle reflections. The data collection technique is to collect test scores that are carried out at the end of each lesson in each cycle using question instruments (written tests). Observational data is carried out by looking at the activeness of students in the learning process. The data are analyzed by means of percentage statistics. The results showed that there was an increase in the completeness of student learning outcomes from 48.57% in pre-study increased to 68.57% % in cycle I and increased to 85.71% in cycle II. Students' learning activities have increased from the sufficient category to good and the good category has increased to excellent. The application of the number head together model can increase the activities and learning outcomes of Social Sciences in the material Interaction between spaces of countries in the Asian Continent and other continents of class IX MTsN 8 Aceh Besar students for the 2018/2019 Academic Year.